What's in a Label? : Analyzing the Public Response to Labeling GE Salmon - Galloway, Andrea (My University, 2012)
The issue of labeling foods containing genetically engineered (GE) ingredients is central to the controversy over the development of GE plants and animals for human consumption. Currently, the only way for Americans to know whether a food contains GE ingredients is to look for the "certified organic" label; if an ingredient is labeled as "organic," it has not been genetically engineered. Only recently has a food animal been developed using gene splicing technology. The AquAdvantage salmon contains genetic material from two other species, the Chinook salmon (Oncorhynchus tshawytscha), a Pacific Ocean species, and a species of eel known as the ocean pout (Zoarces americanus), growing twice as fast as its nontransgenic counterpart. As part of its approval process for this new food, the Food & Drug Administration (FDA) held an electronic public commenting period to find out whether Americans thought the AquAdvantage salmon should be labeled as a GE food. The purpose of this study was to find out what Americans were saying about this new fish. This study also wanted to assess the extent to which the public understands proposed regulations and influences the FDA's decision making.
Color poster with text, images, graphs, and tables.
Keywords: Food--Labeling; Genetic engineering--Moral and ethical aspects; Science and state--Citizen participation; Posters